The effect of sound levels on attention deficit - Mohamed Aminuddin, Mai Mariam (2013)
This study investigated the effect of sound level on attention deficit by examining the evoked response potentials, i.e., N1 peak. Three sound levels were used as stimulation level i.e., Medium (control), Most Comfortable Loud and Uncomfortable loud. In 10 subjects, the results showed that the reduction of N1 wave is getting lesser as the sound level increases. This shows that less attention deficit at high level of sound. The finding could be used for a basis of developing an awareness system or a diagnostic for mental disorder such schizophrenia.